2017
DOI: 10.1002/eji.201747082
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor alpha variable 12‐2 bias in the immunodominant response to Yellow fever virus

Abstract: The repertoire of human αβ T‐cell receptors (TCRs) is generated via somatic recombination of germline gene segments. Despite this enormous variation, certain epitopes can be immunodominant, associated with high frequencies of antigen‐specific T cells and/or exhibit bias toward a TCR gene segment. Here, we studied the TCR repertoire of the HLA‐A*0201‐restricted epitope LLWNGPMAV (hereafter, A2/LLW) from Yellow Fever virus, which generates an immunodominant CD8+ T cell response to the highly effective YF‐17D vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 49 publications
4
26
0
Order By: Relevance
“…Several studies reported high precursor frequency of T-cells reactive to this epitope [22,23]. Bovay et al recently suggested that recognition of antigenic peptide through the germline-encoded CDR1 loop of the TRAV12 segment is one of the main reasons for high precursor frequency [22]. This hypothesis is supported by our TCR structural modeling and TCR-pMHC docking simulations, as well as by the analysis of the NS4Bspecific T-cell repertoire.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Several studies reported high precursor frequency of T-cells reactive to this epitope [22,23]. Bovay et al recently suggested that recognition of antigenic peptide through the germline-encoded CDR1 loop of the TRAV12 segment is one of the main reasons for high precursor frequency [22]. This hypothesis is supported by our TCR structural modeling and TCR-pMHC docking simulations, as well as by the analysis of the NS4Bspecific T-cell repertoire.…”
Section: Discussionsupporting
confidence: 82%
“…The preferential usage of the TRAV12 family was reported before for TCRs responsive to the NS4B epitope [22,23]. It was speculated [22], that the CDR1α of this V-segment forms contacts with the peptide.…”
Section: Tcr Sequencing Shows the Transition Of Clonotypes Between Mementioning
confidence: 67%
See 1 more Smart Citation
“…More recently, several additional tools that have the potential of contributing to a resolution of some of the above issues have become available. First, bioinformatics and computational approaches have made it clear that chemical and structural features of the TCR complementarity‐determining region 3 (CDR3) can correlate with a specific immune response . This development points to the second development, the employment of which offers promise for learning more about specific cancer patient, TCR CDR3, mutant peptide interactions, namely the vast databases now available representing cancer patient mutant amino acids (aa) and tens of thousands of TCR CDR3s for the corresponding TILs.…”
Section: Introductionmentioning
confidence: 99%
“…The HLA-A*02:01 restricted, YFV NS4B 214-222 -epitope may represent a unique opportunity to address this in an outbred human population: it represents an exquisitely dominant CD8 + T cell response as all 93 HLA-A*02:01-positive donors examined here responded to this epitope and an average of 29% of all activated CD8 + T cells from ex vivo blood samples obtained 2-3 weeks after YFV vaccination were specific for this epitope. It has recently been suggested that this massive response can be explained by the invariant CDR1α loop of TRAV12-2 taking part in the recognition of this epitope (36). In donors, who had donated blood samples at the peak of the response (12-21 days after vaccination), we examined whether the presence of HLA-A*02:01, -A*01:01, or -A*03:01, could be correlated to the strength of CD8 + T cell responses restricted by other restriction elements, in casu all available HLA-B allotypes.…”
Section: Inhibition Of Cd8 + T Cell Responses By Immunodomination In mentioning
confidence: 99%